Entendendo o comportamento canino: estudo das causas de agressão e sua influência na profilaxia da raiva humana - Nunes, Juliana Olivencia Ramalho [UNESP] (2015)
There are many benefits generated from the interaction between humans and animals. Mutual way, there are advantages to humans and animals, and between animals, particularly the dog. However, human company may adversely reflect on canine behavior resulting in aggression which, in turn, represent a serious problem for public health. In this sense, this research proposed to study the attacks of dogs to humans, involving the canine behavior. The study was conducted in the municipality of Descalvado, located in São Paulo, southeastern Brazil, by analyzing data from human attendance records occurred in 2014, obtained from the System for Notifiable Diseases Information (SINAN) as well as direct interviews with people bitten and with the owners of the biter dogs, through a questionnaire. Descriptive analysis was performed with frequencies of study and qualitative analysis with content analysis. In the 142 reports of assaults, the canine species predominated among aggressors (74.4%). Of assault people, 46.5% were adults between 20 and 59 years and owners of the dogs, with 42.2% of the interviewed people. The bite was the predominant type of injury (97.2%) in a unique way (66.4%), superficial (51.8%), mainly in hands and feet (43.6%). The procedure adopted more often for post-exposure prophylactic treatment was the observation of the animal associated with vaccination (68.3%). The biter dogs, 70.2% were male, 67.4% adults, 50% were vaccinated against rabies and 9.4% were sterilized. Among the biter dogs, 41.4% walked inappropriately (loose and unsupervised). 41.5% of the biter dogs acted amicably with those members of the household. A reserved attitude was the most frequent behavior demonstrated by the biter dogs for both people who know the dog (but not residing in the same household), and for people unaware of the dog in 39.1% of the interviews. With children, 34.8% of biter dogs showed like children. Based on the data, the reasons that ...